2023
DOI: 10.3390/rs15225294
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Soil Organic Carbon Estimation: CWT-Random Frog-XGBoost as a Prerequisite Technique for In Situ Hyperspectral Analysis

Jixiang Yang,
Xinguo Li,
Xiaofei Ma

Abstract: Rapid and accurate measurement of the soil organic carbon (SOC) content is a pre-condition for sustainable grain production and land development, and contributes to carbon neutrality in the agricultural industry. To provide technical support for the development and utilization of land resources, the SOC content can be estimated using Vis-NIR diffuse reflectance spectroscopy. However, the spectral redundancy and co-linearity issues of Vis-NIR spectra pose extreme challenges for spectral analysis and model const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Similarly, Ye et al demonstrated the superiority of GBRT and XGBoost over RF in SOC estimation using GF-6 hyperspectral satellite data [61]. Furthermore, Yang Li et al showcased the superiority of XGBoost over the RF algorithm in SOC estimation based on spectrometer observations [56]. In the future, although the denoising methods employed in this study proved to be highly effective, they are regarded as fundamental techniques in the field of noise removal.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Similarly, Ye et al demonstrated the superiority of GBRT and XGBoost over RF in SOC estimation using GF-6 hyperspectral satellite data [61]. Furthermore, Yang Li et al showcased the superiority of XGBoost over the RF algorithm in SOC estimation based on spectrometer observations [56]. In the future, although the denoising methods employed in this study proved to be highly effective, they are regarded as fundamental techniques in the field of noise removal.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, Ye et al demonstrated the superiority of GBRT and XGBoost over RF in SOC estimation using GF-6 hyperspectral satellite data [61]. Furthermore, Yang Li et al showcased the superiority of XGBoost over the RF algorithm in SOC estimation based on spectrometer observations [56].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation